Endophytic Streptomyces population induced by L-glutamic acid enhances plant resilience to abiotic stresses in tomato - Kim, Da-Ran; Kwak, Youn-Sig (Frontiers in Microbiology, 2023)
Endophyte bacteria, which colonize plants including roots, stem, flower, and fruit, it can derive their nutrients from the host, are recognized for their mutualistic relationship with the host plant. They play a critical role in promoting host growth and modulating abiotic stress. Carbon and nitrogen have a significant impact on bacterial population and secondary metabolite production, which are highly specific in various categories such as bacterial growth regulation, anti-compounds production. Application of L-glutamic acid can significantly enhance Streptomyces globisporus population buildup in plants. However, the effectiveness of this population buildup against abiotic stresses such as salinity and drought has not been investigated. Therefore, in this study, we tested the bacteria and their prebiotic activity against salinity and drought stress in tomato plants. Three different amino acids were treated on the tomato plants, and it was observed that L-asparagine and L-proline had a negative effect on plant growth and phenotype, while L-glutamic acid promoted plant growth and increased bacteria population density. The bacteria were found to colonize the rhizosphere and root endosphere, with colonization being promoted by L-glutamic acid. Additionally, Streptomyces was found to have plant growth promotion effects and provided protection against abiotic stresses. Interestingly, L-glutamic acid reduced the damage caused by salinity stress, but not drought stress. These findings suggest that L-glutamic acid plays a role in providing tolerance to salinity stress with the core microbiota, thus the current study demonstrated their prebiotic activity in the agriculture system.